Design, novel quality check and experimental test of an original variable length stepped scarf repair scheme. (1st February 2022) - Damghani, Mahdi; Bolanos, Stephan; Chahar, Amandeep; Matthews, Jason; Atkinson, Gary A.; Murphy, Adrian; Edwards, Timothy
Abstract: The performance of well-established stepped scarf repair schemes for highly loaded composite structures has been studied in previous works. However, none of the proposed repair schemes appear to minimise healthy material removal. Thus, this paper proposes a Variable Length Stepped Scarf (VLSS) scheme, which does just that. In addition, various standard schemes with overlap step length (1/60, 1/45 and 1/30) are studied. Both experimental and simulation (FEA) investigations are undertaken and for the first time, the quality of scarf is inspected by artificial-intelligence based machine vision. The experimental results show the VLSS scheme is comparable to the other repair designs in restoring structural stiffness of the intact structure. The VLSS shows the ability to restore ≈ 95 % stiffness of the pristine structure compared to 91 % of the largest repair scheme (overlap step length = 1 / 60 ). However, the VLSS scheme falls short in restoring the static strength of the structure, with an efficiency of 64 % . By contrast, the largest repair scheme shows a superior strength repair efficiency ≈ 77 % and demonstrates a desirable failure response, i.e. fibre fracture in both repair patch and parent laminate. Highlights: A novel minimum size Variable Length Stepped Scarf (VLSS) and machine vision technique for quality control of scarfed laminates are introduced and performance of VLSS is compared against well-established stepped scarf repair schemes for highly loaded composite structures. The VLSS shows the ability to restore ≈ 95 % stiffness of the pristine structure compared to 91.4 % of the largest repair scheme (overlap step length ≈ 1 / 60 ). The VLSS scheme falls short in restoring the static strength of the structure, with an efficiency of 64 % . The largest repair scheme shows a superior strength repair efficiency ≈ 77 % . The largest repair scheme shows a desirable failure response, i.e. fibre fracture in both repair patch and parent laminate.